Yap regulates glucose utilization and sustains nucleotide synthesis to enable organ growth. (22nd October 2018) - Cox, Andrew G; Tsomides, Allison; Yimlamai, Dean; Hwang, Katie L; Miesfeld, Joel; Galli, Giorgio G; Fowl, Brendan H; Fort, Michael; Ma, Kimberly Y; Sullivan, Mark R; Hosios, Aaron M; Snay, Erin; et al.
Abstract: The Hippo pathway and its nuclear effector Yap regulate organ size and cancer formation. While many modulators of Hippo activity have been identified, little is known about the Yap target genes that mediate these growth effects. Here, we show that yap −/− mutant zebrafish exhibit defects in hepatic progenitor potential and liver growth due to impaired glucose transport and nucleotide biosynthesis. Transcriptomic and metabolomic analyses reveal that Yap regulates expression of glucose transporter glut1, causing decreased glucose uptake and use for nucleotide biosynthesis in yap −/− mutants, and impaired glucose tolerance in adults. Nucleotide supplementation improves Yap deficiency phenotypes, indicating functional importance of glucose‐fueled nucleotide biosynthesis. Yap‐regulated glut1 expression and glucose uptake are conserved in mammals, suggesting that stimulation of anabolic glucose metabolism is an evolutionarily conserved mechanism by which the Hippo pathway controls organ growth. Together, our results reveal a central role for Hippo signaling in glucose metabolic homeostasis. Synopsis: The Hippo pathway has emerged as a master regulator of organ size control. Here, genetic models combined with in vivo metabolomic flux analyses identify Yap as a conserved regulator of glucose metabolism, fueling organogenesis but at the same time acting as a gatekeeper of anabolism against energetic stress. Yap is required for optimal liver growth and hepatoblast development in zebrafish. Yap regulates expression of the glucose transporter Glut1 in vivo . Yap‐deficient embryos exhibit decreased glycolytic flux into nucleotide biosynthesis. Metabolic intervention by deoxynucleoside addition rescues the Yap‐deficiency growth phenotype. Regulation of glut1 and glucose uptake by Yap is conserved in mouse hepatocytes. Abstract : Hippo signaling controls glucose uptake and energy metabolism required for liver homeostasis in zebrafish and mouse.